Poverty and mental health: policy, practice and research implications. (October 2020) - Knifton, Lee; Inglis, Greig
Summary: This article examines the relationship between poverty and mental health problems. We draw on the experience of Glasgow, our home city, which contains some of Western Europe's areas of greatest concentrated poverty and poorest health outcomes. We highlight how mental health problems are related directly to poverty, which in turn underlies wider health inequalities. We then outline implications for psychiatry.